2015
DOI: 10.2174/1389450116666150102113648
|View full text |Cite
|
Sign up to set email alerts
|

OPA1 in Cardiovascular Health and Disease

Abstract: Mitochondria are known to play crucial roles in normal cellular physiology and in more recent years they have been implicated in a wide range of pathologies. Central to both these roles is their ability to alter their shape interchangeably between two different morphologies: an elongated interconnected network and a fragmented discrete phenotype -processes which are under the regulation of the mitochondrial fusion and fission proteins, respectively. In this review article, we focus on the mitochondrial fusion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 60 publications
(87 reference statements)
0
13
0
Order By: Relevance
“…According to the summary, we find that under I/R conditions, the actions of mitochondrial fusion proteins on cardiomyocyte apoptosis are tightly associated with the underlying mechanisms. Mitochondrial fusion proteins have fusion effects and non‐fusion effects (Burke, Hall, & Hausenloy, ; Ong et al, ). The protective effects of fusion proteins on cardiomyocytes upon I/R depend on their fusion effects.…”
Section: The Role Of Mitochondrial Fusion and Fission In Cardiomyocytmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the summary, we find that under I/R conditions, the actions of mitochondrial fusion proteins on cardiomyocyte apoptosis are tightly associated with the underlying mechanisms. Mitochondrial fusion proteins have fusion effects and non‐fusion effects (Burke, Hall, & Hausenloy, ; Ong et al, ). The protective effects of fusion proteins on cardiomyocytes upon I/R depend on their fusion effects.…”
Section: The Role Of Mitochondrial Fusion and Fission In Cardiomyocytmentioning
confidence: 99%
“…Mitochondrial fusion proteins have fusion effects and non-fusion effects (Burke, Hall, & Hausenloy, 2015;. The protective effects of fusion proteins on cardiomyocytes upon I/R depend on their fusion effects.…”
Section: Mitochondrial Fusion and Apoptosis Induced By I/rmentioning
confidence: 99%
“…The activity of the IMM pro-fusion protein OPA1 is regulated by alternative splicing and post-translational modification (for a more detailed review please see [112]). In addition to its pro-fusion effects OPA1 has been demonstrated to display a number of pleiotropic non-fusion effects.…”
Section: Mitochondrial Fusion Proteinsmentioning
confidence: 99%
“…In this regard, the discovery of other components of the mitochondrial fission machinery such as ER-mediated mitochondrial pre-constriction and the Drp1 docking proteins in the OMM, Mff and MiD49/51, may provide novel therapeutic targets for inhibiting mitochondrial fission. It is important to appreciate that although acute inhibition of mitochondrial fission induced by acute IRI is cardioprotective, the chronic inhibition of Drp1 may be detrimental to the heart as the process of mitochondrial fission is necessary for the removal of damaged mitochondria by mitophagy [112, 196]. This was nicely illustrated by Ikeda et al [83] who demonstrated that conditional cardiac-specific ablation of Drp1 induced mitochondrial elongation, suppressed mitophagy, increased MPTP opening susceptibility, resulting in a cardiomyopathy and increased MI size following acute IRI.…”
Section: Mitochondrial Fusion and Fission Proteins In Cardiac Health mentioning
confidence: 99%
“…Consequently, these and other studies have inspired an interest in developing strategies to regulate Opa1 expression and function; for a comprehensive account of Opa1 as a therapeutic target in the heart, see Burke et al . (). Cleavage of Opa1‐L to form Opa1‐S with removal of the transmembrane anchor occurs under stress conditions in response to pro‐apoptotic stimuli, loss of membrane potential and drop in ATP levels (Baricault et al, ).…”
Section: Electron Tomography and Mitochondrial Membrane Structurementioning
confidence: 97%